Bathymetry and Shallow Seismic Imaging of the 2018 Flank Collapse of Anak Krakatau - Priyanto, Wisnu S.; Hunt, James E.; Hanif, Muhammad; Tappin, David R.; Permana, Haryadi; Susilohadi,; Cassidy, Michael; Yulianto, Eko (Frontiers in Earth Science, 2021)
The flank failure and collapse of Anak Krakatau on December 22nd, 2018 triggered a destructive tsunami. Whether the prior activity of the volcano led to this collapse, or it was triggered by another means, remains a challenge to understand. This study seeks to investigate the recent volcano submarine mass-landslide deposit and emplacement processes, including the seafloor morphology of the flank collapse and the landslide deposit extent. Bathymetry and sparker seismic data were used during this study. Bathymetry data collected in August, 2019 shows the run-out area and the seafloor landslide deposit morphology. Bathymetry data acquired in May, 2017, is used as the base limit of the collapse to estimate the volume of the flank collapse. Comparisons between seismic data acquired in 2017 and 2019 provide an insight into the landslide emplacement processes, the deposit sequence, and structure below the seafloor. From these results we highlight two areas of the submarine-mass landslide deposit, one proximal to Anak Krakatau island (~1.6 km) and one distal (~1.4 km). The resulting analysis suggests that the submarine-mass landslide deposit might be produced by a frontally compressional, faulted, landslide, triggered by the critical stability slope, and due to the recent volcanic activity. Blocky seabed features clearly lie to the southwest of Anak Krakatau, and may represent the collapse blocks of the landslide. The seismic analysis of the data acquired in August, 2019 reveals that the blocky facies extends to ~1.62 km in the width around Anak Krakatau, and the block thicknesses vary up to 70.4 meters. The marine data provides a new insight into the landslide run out and extent, together with the landslide deposit morphology and structure that are not available from satellite imagery or subaerial surveys. We conclude that the landslide run out area southwest of the recent collapse, is ~ 7.02 ± 0.21 km2.